Optimalisasi Kepercayaan Ibu Menyusui Pada Masa Pandemi Covid-19 di Puskesmas Rejosari Kota Pekanbaru - Komaria Susanti; Lisviarose Lisviarose; Rani Rur Setya Ningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
Mother's Milk (ASI) is the first, main, and best food for babies, which is natural. In the midst of the COVID-19 Pandemic situation, full awareness of infection prevention, especially the COVID-19 virus, is very important, one of which is for breastfeeding mothers. Breastfeeding itself is very important in preventing the transmission of COVID-19 to babies because breast milk contains antibodies that can strengthen the immune system for babies so they are not susceptible to disease. The purpose of this community service activity is to increase the understanding of breastfeeding mothers in exclusive breastfeeding during the COVID-19 pandemic. Problems faced Lack of understanding of mothers about exclusive breastfeeding during the COVID-19 pandemic. The solution offered to this problem is to conduct breastfeeding education counseling during the covid-19 pandemic and an integrated approach is carried out from the initial process of socialization and planning during the activity. In addition, the training method used is the Training of Trainer (TOT) Method with how to provide material using leaflets. The results and the resulting output is that there is an increased understanding of breastfeeding during the COVID-19 pandemic